Kunst uit Rotterdam. - Museum Boijmans Van Beuningen, Rotterdam; Architext; Beeren, W.A.L.; Busch, Marion; Donker Duyvis, Paul; Groot, Paul; Janssen, Hans; Moscoviter, Herman; Post, Jacques; Simons, Annette; Terreehorst, Pauline; de Groot, Elbrig (Rotterdam : Museum Boymans Van Beuningen, 1984)
Architext ; Beeren, W.A.L. ; Busch, Marion ; Donker Duyvis, Paul ; de Groot, Elbrig ; Groot, Paul ; Janssen, Hans ; Moscoviter, Herman ; Post, Jacques ; Simons, Annette ; Terreehorst, Pauline ; Dolz, Dora ; Ficheroux, Mathieu ; Gijzen, Wim ; Henkes, Dolf ; Slot, John van 't ; Van Geest, Arie ; Henning, Paul ; Westerik, Co ; van der Kraan, Axel & Helena ; van Munster, Jan ; van der Pennen, Hans ; Roothaan, Steef ; Wijntjes, Erik ; Beckman, Paul ; Hard Werken ; Kaap, Gerald Van Der ; Kalksma, Gea ; Oorebeek, Willem ; Schouten, Lydia ; Stylingteam Rotterdam Bijvoorbeeld ; Bot, Marrie ; linders, Jannes ; Martens, Peter ; Mentzel, Vincent ; Rook, Piet ; OMA ; Quist, Willem G. ; Weeber, Carel
biografie
Kunst uit Rotterdam, Museum Boymans Van Beuningen, Rotterdam, 1984
Nederlands
kunstcatalogus
Keywords: Nederland; Rotterdam